Finite volume model for labyrinth seal in centrifugal compressor - Andrey V. Nikulchikov; Viktor K. Nikulchikov; Viktor A. Solonenko; Grigoriy R. Ziyakaev; Evgeniy N. Paskov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2025)
Relevance. To date, an urgent issue in the oil and gas industry is to increase the efficiency and the cost-effectiveness of turbomachines by increasing the efficiency of individual units. One way to improve efficiency is to reduce parasitic gas leaks from the turbomachine body. In conditions of high angular velocities and large pressure drops, non-contact labyrinth seals are used. They are a simple and reliable means of preventing gas leaks, despite their low tightness. During the modernization of the centrifugal turbocharger in production, it became necessary to increase the efficiency of the end seals in order to increase the reliability of their operation and increase the overhaul period of the compressor unit. To this end, a project was developed for modified end seals using barrier and buffer gases to minimize contamination of the end seals. Aim. Verification of the proposed design solutions and calculation of the mass flow rate of gases entering and leaving the sealing system of the intermediate pressure stage of a centrifugal turbocompressor at a gap value of 0.5 and 0.35 mm. Objects. Design of the labyrinth seal of turbocompressor intermediate pressure stage, influence of the gap in labyrinth seal on the volume flow rate of gases. Methods. Finite volume method. Results. The authors have calculated the volumes of incoming and outgoing gases at labyrinth seal gaps values of 0.5 mm and 0.35 mm.